Modeling engine spray and combustion processes - Stiesch, Gunnar (Springer-Verlag Berlin, 2003)
The utilization of mathematical models to numerically describe the performance of internal combustion engines is of great significance in the development of new and improved engines. Today, such simulation models can already be viewed as standard tools, and their importance is likely to increase further as available computational power is expected to increase and the predictive quality of the models is constantly enhanced. This book describes and discusses the most widely used mathematical models for in-cylinder spray and combustion processes, which are the most important sub-processes affecting engine fuel consumption and pollutant emissions. The relevant thermodynamic, fluid dynamic, and chemical principles are summarized, and then the application of these principles to the in-cylinder processes is explained. Different modeling approaches for each sub-process are compared and discussed with respect to the governing model assumptions and simplifications. Conclusions are drawn as to which model approach is appropriate for a specific type of problem in the development process of an engine. Hence, this book may serve both as a graduate-level textbook for combustion engineering students and as a reference for professionals employed in the field of combustion engine modeling. The research necessary for this book was carried out during my employment as a postdoctoral scientist at the Institute of Technical Combustion (ITV) at the University of Hannover, Germany, and at the Engine Research Center (ERC) at the University of Wisconsin-Madison, USA.
Keywords: Combustion -- Mathematical models